+0  
 
0
289
3
avatar

$${{log}}_{{\mathtt{0.5}}}{\left({\mathtt{19}}\right)}{\mathtt{\,\small\textbf+\,}}{{log}}_{{\mathtt{2}}}{\left({\mathtt{19}}\right)} = {\mathtt{0}}$$

how to explain this?

Guest Jan 6, 2015

Best Answer 

 #2
avatar+85819 
+10

Here's a slightly different approach to Melody's

Note that we can write .5  as 1/2  = 2-1 

So we have

log2(19)  + log0.5 (19)   .....and...using the"change of base" rule, we can write

log(19) / log(2)  +  log(19) / log(.05) =

log(19) / log(2)  + log(19) / log(1/2) =

log(19) / log(2)  +  log(19) / log2-1 =

log(19) / log(2)  +  log(19) / (-1) log2 =

log(19) / log(2)  +  [ (-1) log(19) /  log2 ] = 

log(19) / log(2)  -  log(19) /  log2 =   0

 

 

CPhill  Jan 7, 2015
Sort: 

3+0 Answers

 #1
avatar+92225 
+5

Mmm interesting.

Let 

 

$$\\x=log_{0.5}(19)\qquad and \qquad y=log_2(19)\\
so\\
19=0.5^x\qquad\qquad and \qquad 19=2^y\\
19=(\frac{1}{2})^x\\
2^x=\frac{1}{19}\\
so\\
2^x\times 2^y=\frac{1}{19}\times 19\\
2^x\times 2^y=1\\
2^x\times 2^y=2^0\\
2^{x+y}=2^0\\
$therefore$\\
x+y=0\\
so\\
log_{0.5}(19)+log_2(19)=0$$

Melody  Jan 7, 2015
 #2
avatar+85819 
+10
Best Answer

Here's a slightly different approach to Melody's

Note that we can write .5  as 1/2  = 2-1 

So we have

log2(19)  + log0.5 (19)   .....and...using the"change of base" rule, we can write

log(19) / log(2)  +  log(19) / log(.05) =

log(19) / log(2)  + log(19) / log(1/2) =

log(19) / log(2)  +  log(19) / log2-1 =

log(19) / log(2)  +  log(19) / (-1) log2 =

log(19) / log(2)  +  [ (-1) log(19) /  log2 ] = 

log(19) / log(2)  -  log(19) /  log2 =   0

 

 

CPhill  Jan 7, 2015
 #3
avatar+92225 
0

Thanks Chris 

It is always good to get a couple of different takes  

Melody  Jan 7, 2015

21 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details